2013
DOI: 10.4012/dmj.2012-155
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of an orthodontic bracket coated with an nitrogen-doped TiO2-xNy thin film and examination of its antimicrobial performance

Abstract: A bracket coated with a nitrogen-doped (N-doped) TiO 2-x N y thin film was prepared using the RF magnetron sputtering method. The physicochemical properties of the thin film were measured using X-ray diffraction and energy-dispersive X-ray spectrometry, while the antimicrobial activity of the bracket against common oral pathogenic microbes was assessed on the basis of colony counts. The rate of antimicrobial activity of the bracket coated with nano-TiO 2-x N y thin film against Streptococcus mutans, Lactobacil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
63
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 14 publications
4
63
0
1
Order By: Relevance
“…Although the silver and titanium coatings differed significantly in antimicrobial activity, their differences were not clinically noticeable. Our results regarding the effect of titanium oxide on bacterial growth were also in line with previous two studies (Cao et al, ; Özyıldız et al, ). Cao et al () sputtered a thin film of nitrogen‐doped titanium oxide, and reported about 95% antimicrobial activity against S mutans (Özyıldız et al, ) coated a layer of titanium oxide over ceramic orthodontic brackets were coated with a layer of TiO 2 and reported effective reductions in S mutans count compared to control (about 98% efficacy).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although the silver and titanium coatings differed significantly in antimicrobial activity, their differences were not clinically noticeable. Our results regarding the effect of titanium oxide on bacterial growth were also in line with previous two studies (Cao et al, ; Özyıldız et al, ). Cao et al () sputtered a thin film of nitrogen‐doped titanium oxide, and reported about 95% antimicrobial activity against S mutans (Özyıldız et al, ) coated a layer of titanium oxide over ceramic orthodontic brackets were coated with a layer of TiO 2 and reported effective reductions in S mutans count compared to control (about 98% efficacy).…”
Section: Discussionsupporting
confidence: 93%
“…Thus, it seems an exotic choice to be used as an antimicrobial agent (Arash et al, 2015a;Berger, Spadaro, Chapin, & Becker, 1976;Silver, 2003). Titanium compounds are other materials shown to have antimicrobial activity (up to about 98% reduction in S. mutans) when coated over orthodontic brackets (Cao, Wang, Li, Liu, & Zhang, 2013;€ Ozyıldız et al, 2010).…”
mentioning
confidence: 99%
“…41 Good antiadhesive properties against Streptococcus mutans were also reported for TNPs in a previous study. 42 It was shown that incorporating TiO 2 nanoparticles into composite resins conferred antibacterial properties to them. However, the mean shear bond strength of composite containing 10% NPs was lower than that of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Titanium dioxide as a photocatalyst, with several excellent properties such as chemical stability [12], biocompatibility [13,14], high potential for self-cleaning [15,16], and high antibacterial activity [17][18][19], has been investigated for applications in various antimicrobial materials [20][21][22]. However, it can only work under ultraviolet(UV)light(wave length <388nm)due to its wide band gap of 3.2eV for anatase TiO 2 [23].…”
Section: Introductionmentioning
confidence: 99%
“…According to the calculated densities of state in anion-doping of anatase TiO 2 crystals, N-doping is the most effective method to enhance the visible light photocatalytic activity of TiO 2 [34][35][36]. It was confirmed that N-doping can extend the optical absorption edge of TiO 2 into the visible-light region, and narrow its band gap [38] , thus enhancing the photocatalytic antibacterial ability of TiO 2 [29] In our previously study, we successfully prepared N-doped TiO 2 thin film on stainless steel brackets using the RF magnetron sputtering method and found that the bracket coated with N-doped TiO 2 thin film showed high antimicrobial and bacterial adhesive properties against normal oral pathogenic bacterial through visible light, which may be effective for the prevention of enamel demineralization and gingivitis during orthodontic treatment [17,19]. It was confirmed that N-doping can extend the optical absorption edge of TiO 2 into the visible-light region, and narrow its band gap [38] , thus enhancing the photocatalytic antibacterial ability of TiO 2 [29] In our previously study, we successfully prepared N-doped TiO 2 thin film on stainless steel brackets using the RF magnetron sputtering method and found that the bracket coated with N-doped TiO 2 thin film showed high antimicrobial and bacterial adhesive properties against normal oral pathogenic bacterial through visible light, which may be effective for the prevention of enamel demineralization and gingivitis during orthodontic treatment [17,19].…”
Section: Introductionmentioning
confidence: 99%